Influence of the PVA fibers and SiO2 NPs on the structural properties of fly ash based sustainable geopolymer. (10th March 2018) - Xu, Shilang; Malik, Muhammad Akbar; Qi, Zhang; Huang, BoTao; Li, Qinghua; Sarkar, Manas
Highlights: Nano silica and fly ash are used as binder material. Different amounts of PVA fibers are introduced in the matrix. The strengths of all geopolymers increased with the fibers. The optimum 5% PVA fibers in the geopolymer system gives the best results. The durability properties were improved significantly in fiber embedded specimens. Abstract: The industrial waste product, fly ash, in presence of alkali activator (NaOH + Na2 SiO3 ) has been utilized with amendment of polyvinyl alcohol (PVA) fibers and 6% nano silica to develop a better sustainable geopolymer. The mechanical, structural and durability properties were increased considerably after the treatment of PVA fibers (3%, 5% and 7%) in nano-silica modified geopolymers at ambient temperature. Most significant activities were observed in 5% PVA fibers incorporated geopolymers (5PCC). Microstructural analysis confirmed the regular distribution of PVA fibers and silica nanoparticles in 5PCC matrix showing least porous and most dense structure responsible for durability and strength enhancement.